Large endometrial polyp with endometrial cancer degeneration filling the uterine cavity: a case report and literature review - Kaczorowska, Anna; Suzin, Jacek; Wojda, Katarzyna; Strużycki, Krzysztof; Sobkiewicz, Sławomir; Lech, Waldemar; Kazimierak, Wojciech (Menopause Review/Przegląd Menopauzalny, 2004)
The common endometrial polyp is made up of endometrial tissue. The main symptoms presented by women in such cases include abnormal uterine bleeding. Such polyps may be single or multiple, small or large enough to fill the uterine cavity. The rate of malignant degeneration in such cases increases with age and size of polyps. In the paper we described a case of large endometrial polyp with malignant degeneration filling the whole uterine cavity. We concluded that the low rate of such cases makes the diagnosis difficult.